Emotional Freedom Therapy (EFT) As an Effort To Improve Post Partum Mother's Preparedness In Facing Pre-Disaster - Sofia Februanti; Tetet Kartilah (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Indonesia is a country that is vulnerable to natural disasters. Natural disasters cannot be predicted when they will occur. Natural disasters can impact anyone, children, parents, adults, pregnant women, giving birth, and breastfeeding women. The impact of natural disasters can cause anxiety at various ages, including postpartum mothers. If this happens, the mother may experience a decrease in breast milk production so that exclusive breastfeeding fails. This community service aims to increase the knowledge and skills of postpartum mothers and cadres regarding EFT in reducing maternal anxiety and increasing the smooth production of breast milk. Activities were carried out in Setiawargi village, Tasikmalaya city. The method used is training in small groups, using demonstration techniques by service providers and re-demonstration by postpartum mothers and cadres. The media used in the training are audio-visual broadcast materials and EFT videos. The activity results showed an increase in the knowledge and skills of postpartum mothers and cadres regarding EFT in reducing maternal anxiety and increasing the smoothness of breast milk production as preparedness in facing pre-disaster conditions.